Cephalometric appraisal of Class II treatment effects after functional and fixed appliances: a retrospective study. (14th October 2016) - Zelderloo, Aurelia; Cadenas de Llano-Pérula, Maria; Verdonck, Anna; Fieuws, Steffen; Willems, Guy
Summary: Objective: To assess the dental, skeletal, and profile changes after functional appliances and subsequent fixed appliances treatment in order to quantify their effect and evaluate the influence of initial incisal inclination and growth pattern. Materials and methods: A retrospective cephalometric analysis was performed in 125 patients (77 females and 48 males). Three lateral cephalograms per patient were available: before treatment (T0, mean age 11.9 years), after functional treatment (T1, mean age 12.9 years), and after fixed appliances (T2, mean age 14.8 years). Results: At T1, a decrease of SNA (0.38° ± 0.77, P < 0.05), an increase of SNB (1.46° ± 0.66, P < 0.05), and a less convex profile (increase N′–Sn′–Pog′ of 2.93° ± 0.87, P < 0.05) were observed as compared to T0. The position of the upper incisors normalizes: initially retroclined upper incisors showed proclination and proclined incisors retroclination. At T1, proclination of the lower incisors was also noticed, being smaller the higher the initial I^NB. At T2, no significant changes in upper and lower incisor position were noticed compared to T1, as well as a decrease of the SNA (1.17° ± 0.75, P < 0.001) and SNB angles (0.41° ± 0.64, P < 0.05) and a stable profile convexity. Conclusion: The improvement of the Class II relationship at T1 was mostly due to dentoalveolar changes: correction of the upper incisor position and proclination of the lower incisors. Skeletal changes were also noticed: constriction of maxillary growth combined with a growth stimulation of the mandible. At T2, no further proclination of the lower incisors was noticed.